Extant life detection using label-free video microscopy in analog aquatic environments - Carl D. Snyder; Manuel Bedrossian; Casey Barr; Jody W. Deming; Chris A. Lindensmith; Christian Stenner; Jay L. Nadeau (PLoS ONE, 2025)
The ability of microbial active motion, morphology, and optical properties to serve as biosignatures was investigated by in situ video microscopy in a wide range of extreme field sites where such imaging had not been performed previously. These sites allowed for sampling seawater, sea ice brines, cryopeg brines, hypersaline pools and seeps, hyperalkaline springs, and glaciovolcanic cave ice. In all samples except the cryopeg brine, active motion was observed without any sample treatment. Active motion was observed in the cryopeg brines when samples were subjected to a temperature gradient above in situ. In general, levels of motility were low in the field samples collected at temperatures <  4ºC. Non-motile cells could be distinguished from microminerals by differences in passive motion (e.g., density measured by sinking/floating), refractive index and/or absorbance, or morphology in the case of larger eukaryotes. Dramatic increases in the fraction of motile cells were seen with simple stimuli such as warming or the addition of L-serine. Chemotaxis and thermotaxis were also observed in select samples. An open-source, autonomous software package with computational requirements that can be scaled to spaceflight computers was used to classify the data. These results demonstrate the utility of volumetric light microscopy for life detection, but also suggest the importance of developing methods to stimulate cells in situ and process data using the restrictions imposed by mission bandwidth, as well as instruments to capture cell-like objects for detailed chemical analysis.